(3OhQ GdGYdGe GdQjGVj GdeQFj aj GfLGM eTQhY GdGMJQGa GdeQFj aj GfLGM eTQhY GdGMJQGa GdQjGVj aj cQI GdbOe HGdLRGFQ s - (3MeOGO , hdjOs; (3YeGQj, eMeOs; (3eYgO GdJQHjI GdHOfjI h GdQjGVjI, LGeYI GdLRGFQ (B3 s ((3GdLRGFQ s, 2023)
(3MGhdfG aj gPg GdOQGSI Cf fJfGhd cjajI eSGgeI MUI (B100% (3ahJ GdJj JHK Ydi GdbfGI GdJdaRjhfjI (B"(3GdgOGa (BTV" (3aj EfLGM eTQhY GdGMJQGa aj cQI GdbOe GdLRGFQjI, hcja GfYcS Pdc Ydi JWhQ cQI GdbOe GdLRGFQjI, hJfWdb gPg GdOQGSI ef CQVjI GdeeGQSI GdUMajI, MjK SYJ Edj GdJYqQa Ydj cjajGJ JfGhd GdEYdGe GdQjGVj GdeQFj deTQhY GdGMJQGa GdQjGVj aj cQI GdbOe GdLRGFQjI, hGQJCjfG OQGSI JMdjd eVGejf heMJhjGJ GdHQfGeL GdQjGVj GdJdaRjhfj GdeJNUU (B"100% (3ahJ(B"(3, hcjajI JYGed GdUMaj GdQjGVj eY Vjhag GddGYHjf Ch GdEOGQjjf Ch GdeOQHjf Ch GdeMddjf hGdNHQGA aj GdejOGf, hcPdc WQjbI GSJYGfJg HeNJda GdeUGOQ hJfhjYgG heOi GfYcGS cd gPG Ydi JWhjQ GdefXheI GdGMJQGajI aj HdGOfG, hPdc dfRY HYV GdZehV GdPj TGH HYV GdfbGW aj gPg GdOQGSI(B.s
(3OcJhGgs
Keywords: (3GYdGe h GJUGd QjGVjs; (3GdGYdGe GdQjGVjs; (3GdGYdGe GdeQFjs